Optimizing Housing Renovation Assistance Programs for the Empowerment of Impoverished Communities in Pacitan Regency: An Islamic Community Development Perspective - Mahendra, Anton Sri; Agustiani, Happy (KOMUNITAS, 2025)
This study explores the optimization of housing renovation assistance programs as a means of empowering impoverished communities in Pacitan Regency, analyzed through the lens of Islamic community development. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving program beneficiaries, local authorities, and implementing stakeholders.  The program embodies core Islamic values, including ukhuwah (social solidarity), ta’awun (mutual assistance), and principles of social justice, aligning with the broader objectives of maqashid sharia, particularly the protection of life (hifz al-nafs), property (hifz al-mal), and family welfare (hifz al-nasl). Despite these positive outcomes, challenges persist, including limited financial resources, inequitable beneficiary selection, and insufficient community engagement during program planning and decision-making processes. Participatory approach that involves collaboration between government entities, religious institutions, and civil society to ensure sustainable, value-driven community empowerment